Translation, cultural adaptation, and validation of the Indonesian version of Pediatric Quality of Life Inventory Rheumatology Module (PedsQL-RM) questionnaire for children with rheumatic diseases - Ganda Ilmana; Zakiudin Munasir; Novie Amelia Chozie; Bernie Endyarni Medise (Indonesian Pediatric Society, 2023)
Background Quality of life is an important outcome in the management of children with chronic conditions such as rheumatic diseases. The Pediatric Quality of Life Inventory Rheumatology Module (PedsQL-RM) questionnaire has been proven valid and reliable, but a validated Indonesian version of the questionnaire is not yet available. Objective To translate the PedsQL-RM into the Indonesian language, perform a transcultural adaptation, and assess its validity. Methods A cross-sectional study was performed in patients aged 2 to 18 years with systemic lupus erythematosus (SLE) or juvenile idiopathic arthritis (JIA) in Dr. Cipto Mangunkusumo Hospital, Jakarta. The initial phase of the study consisted of forward translation from the original English version into Indonesian, synthesis by experts, backward translation, and cognitive debriefing, resulting in the final version of the questionnaire. The second phase was testing the final questionnaire on patients in each age group and their parents. Tests were carried out in two sessions with an interval of 2 to 4 weeks. The questionnaire consisted of a child report and a parent report, each measuring five dimensions: pain and hurt, activities, treatment, worry, and communication. We subsequently assessed validity and reliability of each dimension in the child and parent reports for the child and teen age groups. Validity was expressed as correlation coefficient (r) between dimension scores with the total score. Results The finalized Indonesian questionnaire was completed by 53 children aged 2-18 years with SLE or JIA and their parents. Due to small numbers of subjects in the younger age ranges, analysis was only performed in the 8-to-18-year age group. Validity varied from good to very good (r = 0.437 to 0.910) for the child report and from poor to good (r = 0.153 to 0.808) for the parent report. The questionnaire was deemed reliable, with a Cronbach’s alpha of 0.755 to 0.785. Conclusion The Indonesian version of the PedsQL-RM is valid and reliable for assessing quality of life in children aged 8 to 18 years with rheumatologic disease. Further study is needed to assess the validity and reliability of the tool for children aged 2 to 7 years.